Central banking for financial stability in Asia - Masahiro Kawai; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2012)
A key lesson of the 2007 - 2009 global financial crisis (GFC) was the importance of containing systemic financial risk and the need for a "macroprudential" approach to surveillance and regulation that can identify system-wide risks and take appropriate actions to maintain financial stability. By virtue of their overview of the economy and the financial system and their responsibility for payments and settlement systems, there is a broad consensus that central banks should play a key role in monitoring and regulating financial stability. Emerging economies face additional challenges because of their underdeveloped financial systems and vulnerability to volatile international capital flows, especially "sudden stops" or reversals of capital inflows. This paper reviews the recent literature on this topic and identifies relevant lessons for central banks, especially those in Asia's emerging economies. Major topics discussed include the debate about the definition of financial stability, the consistency of a financial stability objective with the more traditional and well-established central bank objective of price stability, the appropriate governance structure for coordination of macroprudential policy with other financial supervisors and entities, and the appropriate policy instruments to achieve macroprudential policy objectives, including conventional, unconventional, and macroprudential tools. Finally, the paper considers issues involved with regional financial regulatory cooperation. Overall, the report concludes that the "lean versus clean" debate has been resolved largely in favor of the former, and that central banks should have a financial stability mandate and the policy tools to successfully pursue that mandate.
Keywords: E52; F31; G28; 330; central banking; central banks; financial stability; asia; surveillance and regulation; global financial crisis; Finanzkrise; Bankenaufsicht; Geldpolitik; Zentralbank; Finanzmarktregulierung; Welt